Underfunding Annual Pension Contributions: Examining the Factors Behind an Ongoing Fiscal Phenomenon. (March 2015) - Thom, Michael; Randazzo, Anthony
Inadequate contributions are one factor behind the gap between pension assets and benefit liabilities. Each year, many states fail to meet their required pension contribution while others consistently meet or exceed their required amount. This study seeks to identify the factors that shape actual pension contributions across the states. Results suggest that states with smaller long-term funding gaps are more likely to fund required contributions. Legislative professionalism and constitutional collective bargaining privileges reduce annual funding. The effect of partisan and institutional traits was sensitive to methodology. Revenue changes and balanced budget requirements had no significant effect on pension contributions. These results suggest a number of reform avenues, including constitutional, institutional, and programmatic changes of varying political feasibility.